Deep Learning Based Coding And Artificial Intelligence For Computational Thinking In Elementary Schools: Pembelajaran Koding Dan Kecerdasan Artifisial Berbasis Pembelajaran Mendalam Untuk Berpikir Komputasional Siswa Sekolah Dasar - Ainul Mardhiyah; Muhamad Sofian Hadi; Misriandi Misriandi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The rapid advancement of digital technology requires elementary education to cultivate higher-order thinking and digital literacy as foundational competencies for the twenty-first century. Specific Background: Coding and artificial intelligence learning have been introduced in elementary schools as concrete approaches to support computational thinking through meaningful and contextual learning experiences. Knowledge Gap: Previous studies in Indonesia largely emphasize technical implementation or teacher training, while limited attention has been given to pedagogical strategies grounded in deep learning approaches for fostering computational thinking at the elementary level. Aims: This study explores deep learning–based coding and artificial intelligence learning strategies for developing computational thinking among elementary school students in North Serpong District. Results: Using a descriptive qualitative approach involving teachers and students from two elementary schools, the findings indicate that learning strategies emphasizing active participation, problem solving, reflection, and contextual activities support students’ ability to decompose problems, recognize patterns, construct abstractions, and formulate algorithmic steps. Variations in computational thinking development were observed across schools, reflecting differences in learning implementation quality. Novelty: This study confirms that deep learning–based coding and artificial intelligence learning demonstrates differentiated reinforcement across computational thinking dimensions according to contextual implementation in elementary classrooms. Implications: The findings position deep learning–based coding and artificial intelligence as a strategic pedagogical alternative for strengthening computational thinking and digital literacy within elementary education. Highlights • Computational Thinking Developed Through Contextual Coding Activities• Deep Learning Approach Supports Reflective And Meaningful Learning• Differentiated Implementation Shapes Student Learning Outcomes Keywords Coding Learning; Artificial Intelligence; Deep Learning; Computational Thinking; Elementary School